Creating a digital twin for a production logistics model system using Discrete Event Simulation - Munkácsi, István; Skapinyecz, Róbert (Advanced Logistic Systems - Theory and Practice, 2026)
The aim of the paper is to present the creation process of a digital twin based on discrete-event simulation for a production logistics model system. The given system is located in the Logistics 4.0 Laboratory of the Institute of Logistics of the University of Miskolc. It consists of an automated, PLC-controlled material handling system based on roller conveyors and turntables, which is supplemented by a gravity flow rack. It also has multiple locations along the conveyor track that could serve as storage or assembly stations. A real-scale model of the entire system was created with the aid of Siemens Tecnomatix Plant Simulation. In the developed model, proprietary methods control the transfer of raw materials, congestion management and the operation of the turntables. Based on the operation of the complete system, the simulation examines machine utilization, human resources and bottlenecks in the material flow. The results demonstrate the advantages of using discrete-event simulation based digital twins for the optimization of production logistics systems.